2022
DOI: 10.1002/adom.202201921
|View full text |Cite
|
Sign up to set email alerts
|

Surface Doping Boosts Triplet Generation Yield in Perovskite‐Sensitized Upconversion

Abstract: Triplet–triplet annihilation‐based photon upconversion (TTA‐UC) can efficiently generate higher energy photons at low relative fluences. Bulk metal halide perovskites have offered promise in efficiently sensitizing molecular triplet states in the solid state, necessary for the integration of TTA‐UC into device‐based applications. Recent work focused on TTA‐UC from a rubrene triplet annihilator sensitized by perovskite thin films has established relatively efficient charge extraction from the perovskite, formin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 58 publications
1
38
0
Order By: Relevance
“…We have previously shown that this solvent treatment increases triplet generation in rubrene due to n-type doping of the perovskite, which increases the hole density at the surface due to interfacial band bending. 55 Once interfaced with the OSCs, additional spectral features corresponding to the T 1 → T n ESA transitions previously shown in Fig. 1 for both OSCs emerge and can be detected on a sub-nanosecond timescale for both RubDBP (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…We have previously shown that this solvent treatment increases triplet generation in rubrene due to n-type doping of the perovskite, which increases the hole density at the surface due to interfacial band bending. 55 Once interfaced with the OSCs, additional spectral features corresponding to the T 1 → T n ESA transitions previously shown in Fig. 1 for both OSCs emerge and can be detected on a sub-nanosecond timescale for both RubDBP (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…146,147 While ACN can be classified as type I, it is considered its own category as it fully dissolves MAFA perovskites and partially dissolves the FAMA composition. 144 Based on this solvent classification, the previous report of differing effects in the UC PL intensity when depositing rubrene from CB and TOL can simply be traced back to different effects of the solvent on the perovskite surface. 133…”
Section: Mechanistic Insightsmentioning
confidence: 98%
“…Expanding on this approach, we have recently investigated in detail the effect of seven different solvents on the perovskite-sensitized UC mechanism: 144 acetonitrile (ACN), ethanol (EtOH), IPA, 1-butanol (ButOH), TOL, CB and ANI. Following Taylor et al , 145 the solvents can be classified into three categories.…”
Section: Mechanistic Insightsmentioning
confidence: 99%
See 2 more Smart Citations